Pengaruh Keselamatan dan Kesehatan Karyawan Terhadap Kinerja Karyawan PT. Citra Shipyard - Anisa Reskita br Tobing; Jontro Simanjuntak (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2020)
This study aims to optimize employee safety and health on employee performance. There are a number of people aged 140 years who have been able to find the right amount of money. The instrument can also be used to read data data. The sample technical data is random data random data for SPSS version 25. The results of the study are known t arithmetic> t table that is 4,633> 1,9776 and a significant value of 0,000 <0.05. This is a very interesting place to visit in the middle of PT Citra Shipyard. t calculate employee health > t table is 6.483> 1.9776 and a significant value of 0.000 <0.05. This means that employee health is positive and significant for the performance of PT Citra Shipyard's employees. Also, there are safety and health of employees together to strengthen positive and significant impact on employee performance. Evidenced by the results of the F test (simultaneous) F value of 46.729)> 3.06 (F-table) and the value significantly at 0,000 <0.05.